PD-1 blockade with pembrolizumab in classic or endemic Kaposi's sarcoma: a multicentre, single-arm, phase 2 study. Issue 4 (April 2022) - Delyon, Julie; Biard, Lucie; Renaud, Marion; Resche-Rigon, Matthieu; Le Goff, Jérôme; Dalle, Stéphane; Heidelberger, Valentine; Da Meda, Laetitia; Toullec, Laurie; Carcelain, Guislaine; Mourah, Samia; Caillat-Zucman, Sophie; et al.
Summary: Background: Although the treatment of iatrogenic and HIV-related Kaposi sarcoma is well defined and mostly based on restoring immune function, the treatment of classic and endemic Kaposi sarcoma is less well established. Chemotherapy or interferon α is used for patients with extensive cutaneous or visceral Kaposi sarcoma, but tolerance might be poor and long-term remission is rare. We aimed to evaluate the activity of pembrolizumab in classic and endemic Kaposi sarcoma with cutaneous extension requiring systemic treatment. Methods: We did a multicentre, single-arm, proof-of-concept, phase 2 trial in adults aged 18 years or older with histologically proven classic or endemic Kaposi's sarcoma with progressive cutaneous extension requiring systemic treatment and an Eastern Cooperative Oncology Group performance status of 0–1 in three hospitals in France. The patients were treated with 200 mg pembrolizumab intravenously every 3 weeks for 6 months (eight cycles) or until severe toxicity. The primary endpoint was the best overall response rate within the 6-month timeframe, defined by the occurrence of a complete response or partial response and assessed by an investigator using the modified AIDS Clinical Trial Group (ACTG) criteria. Three or more responses among a total 17 patients were needed for the primary endpoint to be met, using a Simon's two-stage optimal design assuming a 30% response rate as desirable. For this final study analysis, all patients were included following the intention-to-treat principle. This study is registered with ClinicalTrials.gov, NCT03469804, and is closed to new participants. Findings: 30 patients were screened for eligibility and 17 patients (eight [47%] with classic and nine [53%] with endemic Kaposi's sarcoma) were enrolled between July 2, 2018, and Dec 16, 2019. The median follow-up was 20·4 months (IQR 18·1–24·1). Two (12%) patients had a complete response, ten (59%) had a partial response, and five (29%) had stable disease as the best response within the 6-month treatment timeframe, with a best overall response rate of 71% (95% CI 44–90), meeting the predefined primary outcome (ie, exceeding a response rate of 30%). Treatment-related adverse events occurred in 13 (76%) of 17 patients, including two grade 3 adverse events (one [6%] acute cardiac decompensation and one [6%] granulomatous reaction). Treatment was prematurely discontinued in two (12%) patients due to grade 3 acute reversible cardiac decompensation and grade 2 pancreatitis, and one other patient had a grade 3 granulomatous reaction in mediastinal lymph nodes requiring steroids and methotrexate treatment. There were no serious adverse events or treatment-related deaths. Interpretation: In this prospective trial, which to our knowledge is the first to assess the role of PD-1 blockade in patients with classic and endemic Kaposi's sarcoma, pembrolizumab showed promising anti-tumour activity with an acceptable safety profile. If this result is supported by further studies, treatment with anti-PD-1 could be part of the therapeutic armamentarium for patients with classic and endemic Kaposi's sarcoma. Funding: MSD France.